A Bibliometric Study of Renewable Energy from Waste - Hastarini Dwi Atmanti; Retno Sugiharti; Rini Handayani (Cita Konsultindo Research Center, 2023)
A bibliometric analysis of waste as a source of renewable energy is the aim of this research. This has to do with the generation of renewable energy from waste. Only English article were chosen, and the data source is Scopus with a 2008-2024time frame. There were 72 papers that were chosen. This study suggests that the generation of renewable energy from waste is a growing area of research.